The Application Of E-Government To Public Policy - H.R. Iip Hidajat; Yeti Rohayati; Pandji Santosa (Jurnal Multidisiplin Sahombu, 2024)
The development and utilization of telematics in the regions is still far from ideal conditions to support e-government policies. This is indicated by the developing conditions that: (1) in general, the people and bureaucracy in the regions still do not understand the importance of e-government programs as a support in improving and facilitating public services. (2) In general, the public, including offices, agencies, agencies and other institutions in the region, have not been able to operate computers as computers function as information technology. (3) Computer equipment is still considered expensive and is not yet needed as a means of information and communication. Bureaucrats and local governments do not have a mature level of readiness to accept e-government policy programs, both in the form of formal legality readiness in the form of legal instruments, human resource readiness, budget readiness, infrastructure readiness and organizational culture readiness. In the model of e-government policy in the regions, the formulation of the model must be built based on the clarity of the vision and mission of the local government to build e-government based on public interests, social conditions and community characteristics. In addition, in formulating models for e- government policies in the regions, it is also necessary to consider economic rationality and bureaucratic rationality